2009
DOI: 10.1021/jp808328a
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Single Protein Polymers To Measure Flexural Rigidity

Abstract: The micrometer-scale length of some protein polymers allows them to be mechanically manipulated in single-molecule experiments. This provides a direct way to measure persistence length. We have used a double optical trap to elastically deform single microtubules and actin filaments. Axial extensional force was exerted on beads attached laterally to the filaments. Because the attachments are off the line of force, pulling the beads apart couples to local bending of the filament. We present a simple mechanical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 52 publications
6
63
0
Order By: Relevance
“…1C). Points along the SFs were spaced ,5 mm apart, which is below the persistence length of F-actin (Arai et al, 1999;Brangwynne et al, 2007;van Mameren et al, 2009). If an SF moved or deformed, a displacement vector was mapped from one of the initial tracking points to a new point on the fibre at the next time step, normal to the initial SF position (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1C). Points along the SFs were spaced ,5 mm apart, which is below the persistence length of F-actin (Arai et al, 1999;Brangwynne et al, 2007;van Mameren et al, 2009). If an SF moved or deformed, a displacement vector was mapped from one of the initial tracking points to a new point on the fibre at the next time step, normal to the initial SF position (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All images of live actin-EGFP transfected cells are maximum intensity Zprojections of the confocal planes that contained SFs (,2-5 mm thick). Points along SFs [separated by ,5 mm, which is less than the persistence length of Factin (Arai et al, 1999;Brangwynne et al, 2007;van Mameren et al, 2009)] were tracked over the course of the experiment. SF displacement was measured at these points as a function of time and averaged over all points for all SFs.…”
Section: Image and Statistical Analysismentioning
confidence: 99%
“…Moreover, they reported that the rise time for kinesin steps in vitro is typically 20-50 ms. Priel et al (2005) showed that the wave may propagate at a speed of 2 nm/ ps ( ¼2000 m/s) along microtubule associated protein 2 (MAP2) with the length of 1 nm (the order of magnitude for wave traveling time¼10 À 12 s). Meanwhile, theoretical models have also been developed for predicting the microtubules mechanics in recent years, including prediction of flexural rigidity van Mameren et al, 2009;Ghavanloo et al, 2010a;Donhauser et al, 2010), elastic buckling (Wang. et al, 2006;Li, 2008;Yi et al, 2008;Chelminiak et al, 2010) and mechanical vibration (Sirenko et al, 1996;Kasas et al, 2004b;Portet et al, 2005;Tounsi et al, 2010;Ghavanloo et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Active methods refer to more direct measurement, e.g., by applying a mechanical load on partially supported MTs and measuring their displacement or strain response. The load exerted on the MTs can be established through fluid flow [10,11], optical tweezers [12][13][14][15][16], atomic force microscope probes [17][18][19][20], rigid barriers [21], membranes [22,23], or even motor proteins [24][25][26][27][28]. One of the most interesting conclusions from these studies is that the bending rigidity D of a MT depends on its contour length L c .…”
Section: Introductionmentioning
confidence: 99%